2013
DOI: 10.2308/accr-50480
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reward Type on Employee Goal Setting, Goal Commitment, and Performance

Abstract: The use of tangible rewards in the form of non-cash incentives with a monetary value has become increasingly common in many organizations (Peltier et al. 2005). Despite their use, the behavioral and performance effects of tangible rewards have received minimal research attention. Relative to cash rewards, we predict tangible rewards will have positive effects on goal commitment and performance but will lead employees to set easier goals, which will negatively affect performance. The overall performance impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 41 publications
0
47
0
7
Order By: Relevance
“…According to some studies, in-kind gifts can be a good alternative to money [33] [34]. However, Shaffer and Arkes [35] concluded that this is only the case when money and in-kind gifts are not offered simultaneously.…”
Section: Personal Incentives Via Smartphone Apps To Cycle To Work Havmentioning
confidence: 99%
“…According to some studies, in-kind gifts can be a good alternative to money [33] [34]. However, Shaffer and Arkes [35] concluded that this is only the case when money and in-kind gifts are not offered simultaneously.…”
Section: Personal Incentives Via Smartphone Apps To Cycle To Work Havmentioning
confidence: 99%
“…In a context when an assigned goal is applied, it is essential to examine the effect of an employee's commitment toward the goal, as it has been indicated by prior studies (Locke & Latham, 2002;Presslee, Vance, & Webb, 2013) that individual's performance would be affected by his/her commitment toward the assigned goal. In line with the goal setting theory (Locke, 1996), an individual's goal commitment therefore becomes an essential factor that initiate motivation and effort, which will subsequently affect performance.…”
Section: Goal Difficulty Goal Commitment and Performancementioning
confidence: 99%
“…♦ Rewards support the organization's culture (Bartol & Srivastava, 2002). Presslee, Vance, and Webb (2013) report that such systems are adaptable to changing business conditions, are clearly communicated and fully understood by employees, and are related to actual business DOI: 10.1002/piq Performance Improvement Quarterly performance. Finally, Randolph and Kemery (2011) believe that such systems allow employees to participate in their design, are regularly reviewed for eff ectiveness in meeting stated goals and objectives, and are perceived by employees as having value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Th e result is motivated, productive employees ready to accept challenges and take initiative for professional development (Bartol & Srivastava, 2002). According to Presslee et al (2013), developmentally oriented managers do not develop employees; they equip employees to develop themselves.…”
Section: Seven Managerial Practicesmentioning
confidence: 99%